Management of the Malignant Middle Cerebral Artery Syndrome - Hwang, David Y.; Matouk, Charles C.; Sheth, Kevin N. (Seminars in Neurology, 2013)
The malignant middle cerebral artery syndrome, characterized by cerebral edema following large anterior circulation ischemic stroke, is a disease entity with high morbidity and mortality that is easy to recognize, but challenging to manage. In this review, we begin by discussing important aspects of the clinical presentation of the syndrome, including risk factors for deterioration. We then discuss medical measures that can be undertaken before symptomatic cerebral edema occurs and then outline both medical and surgical options for subsequent neurologic worsening. Shared decision making with patients' surrogates regarding decompressive craniectomy in the setting of available clinical trial data is addressed. The authors conclude with a brief discussion of promising novel therapies for preventing cerebral edema.
Keywords: middle cerebral artery; stroke; brain edema; decompressive craniectomy; decision making